Prevention of Money Politics and Organizing Quality Elections: An Revitalization of Ideology (Law Research Review Quarterly, 2016)
In modern democracies, the election of political leaders (regional heads) is a matter of concern with political recruitment. Political recruitment itself is a problem that is lined with democracy. Only in a democratic system, the issue of political recruitment becomes an important and strategic issue to be seriously considered. In a monarchic or authoritarian system, this problem is not a major issue. A political leader is easily determined based on lineage (monarchy) or unilateral (authoritarian) power.